Unsur Susastra Dan Gaya Bahasa Dalam Serat Srikandhi Meguru Manah Jilid I - Titin Masturoh (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
Serat Srikandhi Meguru Manah is one source of lakon in puppetry, which is still in Javanese language. Therefore, transliteration and translation become the first steps undertaken in this study. This study aims to understand the meaning, function, and the variety of literary values and language styles contained in the script in the form of Javanese song (tembang). A literary approach is used to analyze the elements of literature and language style. The results of this research are the translation and analysis of literary elements including sasmita tembang, tembung garba, tembung dwilingga and tembung tanggap “na” and also the elements of the language styles: simile, personification, hyperbole, and purwakanthi.Keywords: literature, language style, serat, Srikandhi Meguru Manah